Characters With Exceptionalities Portrayed in Contemporary Canadian Children’s Books - Emmerson, Jean; Brenna, Beverley (Canadian Journal of Education/Revue canadienne de l’éducation, 2015)
This article examines the ways in which exceptionality is addressed in Canadian children’s literature, offering critical literacy as an avenue toward social justice. A content analysis (Berg, 2009) of 134 Canadian children’s books offers a wide scope of contemporary titles to include in classrooms. We developed conceptual categories to explore patterns and trends through a qualitative interpretive stance (Seidman, 2006). Our findings include the following results: • ethnically diverse characters with exceptionalities, • authentic characters with real-world challenges, • fantasy blended with other genres. As narratives that include exceptionalities become more authentic and abundant, we can become more appreciative of diversity, further affecting inclusive schools and communities.